PRAGMATICS FUNCTIONS OF PERLOCUTIONARY ACT IN LEVELED READING BOOK - juliantina - sebayang (STKIP Budidaya Binjai, 2020)
Perlocutionary act is the result of the effect of an utterance. Perlocutionary act brings the hearer to learn something, persuade, deceive, encourage, irritate, frighten, amuse, get the hearer to do something, inspire, impress, distract, get the hearer to think about, relieve tension, embarrass, attract attention, bored. Perlocutionary act is a speech act spoken by a speaker to influence the interlocutors and can be found in the communication process. One form of communication process can be found in conversations between the characters in story from children’s reading book. Perlocutionary act is uttered with different pragmatic functions according to the context of the speech. The objectives of this journal are to describe the functions of perlocutionary act in levelled reading book. The journal approach used pragmatics and qualitative approach.Keyword : perlocutionary act, pragmatic function, levelled reading book